Tìm x biết b/ x^3+4x=0
Bài 1: Tìm x biết a) x^3 - 4x^2 - x + 4= 0 b) x^3 - 3x^2 + 3x + 1=0 c) x^3 + 3x^2 - 4x - 12=0 d) (x-2)^2 - 4x +8 =0
a: \(x^3-4x^2-x+4=0\)
=>\(\left(x^3-4x^2\right)-\left(x-4\right)=0\)
=>\(x^2\left(x-4\right)-\left(x-4\right)=0\)
=>\(\left(x-4\right)\left(x^2-1\right)=0\)
=>\(\left[{}\begin{matrix}x-4=0\\x^2-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x^2=1\end{matrix}\right.\Leftrightarrow x\in\left\{2;1;-1\right\}\)
b: Sửa đề: \(x^3+3x^2+3x+1=0\)
=>\(x^3+3\cdot x^2\cdot1+3\cdot x\cdot1^2+1^3=0\)
=>\(\left(x+1\right)^3=0\)
=>x+1=0
=>x=-1
c: \(x^3+3x^2-4x-12=0\)
=>\(\left(x^3+3x^2\right)-\left(4x+12\right)=0\)
=>\(x^2\cdot\left(x+3\right)-4\left(x+3\right)=0\)
=>\(\left(x+3\right)\left(x^2-4\right)=0\)
=>\(\left(x+3\right)\left(x-2\right)\left(x+2\right)=0\)
=>\(\left[{}\begin{matrix}x+3=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=2\\x=-2\end{matrix}\right.\)
d: \(\left(x-2\right)^2-4x+8=0\)
=>\(\left(x-2\right)^2-\left(4x-8\right)=0\)
=>\(\left(x-2\right)^2-4\left(x-2\right)=0\)
=>\(\left(x-2\right)\left(x-2-4\right)=0\)
=>(x-2)(x-6)=0
=>\(\left[{}\begin{matrix}x-2=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=6\end{matrix}\right.\)
tìm x biết
a)4x^2+4x-3=0
b)x^4-3x^3-x+3=0
c)x^2(x-1)-4x^2+8x-4=0
\(4x^2+4x-3=0\)
\(\left[\left(2x\right)^2+2.2x.1+1\right]-4=0\)
\(\left(2x+1\right)^2-2^2=0\)
\(\left(2x+1-2\right).\left(2x+1+2\right)=0\)
\(\left(2x-1\right).\left(2x+3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x-1=0\\2x+3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=-\frac{3}{2}\end{cases}}}\)
Vậy \(\orbr{\begin{cases}x=\frac{1}{2}\\x=-\frac{3}{2}\end{cases}}\)
\(x^4-3x^3-x+3=0\)
\(x^3.\left(x-3\right)-\left(x-3\right)=0\)
\(\left(x-3\right).\left(x^3-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x^3-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}}\)
Vậy \(\orbr{\begin{cases}x=3\\x=1\end{cases}}\)
\(x^2.\left(x-1\right)-4x^2+8x-4=0\)
\(x^2.\left(x-1\right)-\left[\left(2x\right)^2-2.2x.2+2^2\right]=0\)
\(x^2.\left(x-1\right)-\left(2x-2\right)^2=0\)
\(x^2.\left(x-1\right)-4.\left(x-1\right)^2=0\)
\(\left(x-1\right).\left[x^2-4.\left(x-1\right)\right]=0\)
\(\left(x-1\right).\left[x^2-2.x.2+2^2\right]=0\)
\(\left(x-1\right).\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}}\)
Vậy \(\begin{cases}x=1\\x=2\end{cases}\)
Tham khảo nhé~
tìm x biết
a)4x^2+4x-3=0
b)x^4-3x^3-x+3=0
c)x^2(x-1)-4x^2+8x-4=0
Tìm x biết
a) x^3+4x=0
b) (5-x).2=4x-3
a) \(x^3+4x=0\)
\(\Rightarrow x\left(x^2+4\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x^2+4=0\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x^2=-4\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x\in\phi\end{array}\right.\)
Vậy: \(x=0\)
b) \(2\left(5-x\right)=4x-3\)
\(\Rightarrow10-2x=4x-3\)
\(\Rightarrow10+3=4x+2x\)
\(\Rightarrow13=6x\)
\(\Rightarrow x=\frac{13}{6}\)
x3+ 4x=0
<=> x(x2+4)=0
=> x=0 hoặc x2+4=0
Mà: x2+4 >4
=>x=0
b) (5-x).2=4x-3
<=>10-2x=4x-3
<=>10+3= 2x+4x
<=>13=6x
=>x=\(\frac{13}{6}\)
Tìm x biết a) 3√x - 7 = 0 b) √x-2 + √4x-8=3
\(a,3\sqrt{x}-7=0\left(dk:x\ge0\right)\\ \Leftrightarrow3\sqrt{x}=7\\ \Leftrightarrow\sqrt{x}=\dfrac{7}{3}\\ \Leftrightarrow x=\dfrac{49}{9}\left(tmdk\right)\)
Vậy \(S=\left\{\dfrac{49}{9}\right\}\)
\(b,\sqrt{x-2}+\sqrt{4x-8}=3\left(dk:x\ge2\right)\\ \Leftrightarrow\sqrt{x-2}+\sqrt{4\left(x-2\right)}=3\\ \Leftrightarrow\sqrt{x-2}+2\sqrt{x-2}=3\\ \Leftrightarrow3\sqrt{x-2}=3\\ \Leftrightarrow\sqrt{x-2}=1\\ \Leftrightarrow x-2=1\\ \Leftrightarrow x=3\left(tmdk\right)\)
Vậy \(S=\left\{3\right\}\)
a: =>3*căn x=7
=>căn x=7/3
=>x=49/9
b: =>3*căn x-2=3
=>căn x-2=1
=>x-2=1
=>x=3
`a, 3 sqrt x - 7 = 0`
`<=> 3 sqrt x = 7`
`<=> sqrt x = 7/3`
`<=> x = 49/9`.
Vậy `x = 49/9`
`b, sqrt(x-2) + sqrt(4x-8) = 3`
`<=> sqrt(x-2) + 2 sqrt(x-2) = 3`
`<=> 3 sqrt(x-2) = 3`
`<=> sqrt(x-2)=1`
`<=> x-2=1`
`<=> x = 3`
Vậy `x = 3`
Tìm x , biết
a, 4x-√x=0
b, (√x)^3-x=0
a. \(4x-√x=0\)
<=>√x(4√x-1)=0
<=>4√x-1=0
<=>4√x=1
<=>√x=1/4
<=>x=1/16
b. (√x)^3-x=0
<=>x(√x-1)=0
<=>√x-1=0
<=>√x=1
<=>x=1
Đáp số a. x=1/16
b. x=1
Tìm x biết
a) 25x^2 -1-(5x-1)(x+2) = 0
b) (2x-3)-(3-2x)(x-1) = 0
c) 9 -4x^2-(6+4x)(x-5) = 0
b) ( 2x - 3 ) - ( 3 - 2x )( x - 1 ) = 0
<=> ( 2x - 3 ) + ( 2x - 3 )( x - 1 ) = 0
<=> ( 2x - 3 )( 1 + x - 1 ) = 0
<=> x( 2x - 3 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}x=0\\2x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{3}{2}\end{cases}}}\)
Vậy .....
a, 25x^2 - 1 - (5x -1)(x+2)=0
=> (5x)^2 - 1 + (5x-1)(x+2) = 0
=> (5x-1)(5x+1) + (5x-1)(x+2) = 0
=> (5x-1)(5x+1+x+2) = 0
=> (5x-1)(6x+3) = 0
=> \(\orbr{\begin{cases}5x-1=0\\6x+3=0\end{cases}}\)
a) 25x2 - 1 - ( 5x - 1 )( x + 2 ) = 0
<=> ( 5x - 1 )( 5x + 1 ) - ( 5x - 1 )( x + 2 ) = 0
<=> ( 5x - 1 )( 5x + 1 - x - 2) = 0
<=> ( 5x - 1 )( 4x - 1 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}5x-1=0\\4x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{5}\\x=\frac{1}{4}\end{cases}}}\)
Vậy .......
Tìm số tự nhiên x,biết:
a) x : 13 = 41;
b) 4x : 17 = 0;
c) 8(x - 3) = 0.
a) x : 13 = 41
x=41.13
x=533
b) 4x : 17 = 0
⇒4x=0
⇒x=0
c) 8(x - 3) = 0
⇒x-3=0
x=0+3
x=3
a. x : 13 = 41
<=> x = 41 . 13
<=> x = 533
b. 4x : 17 = 0
<=> 4x = 0
<=> x = 0
c. 8(x - 3) = 0
<=> 8x - 24 = 0
<=> 8x = 24
<=> x = 3
Tìm x biết:
a) x 2 + 3 x = 0 b) x ( 2x − 1) + 4x − 2=0 c) ( x 2 + 2 x )2 − 2 x 2 − 4 x = 3
a. x( x+ 3)= 0
⇔ x= 0 hoặc x+ 3= 0
⇔ x= 0 x = -3
b. x( 2x− 1)+ 2( 2x− 1) =0
⇔ ( 2x− 1)(x+ 2) =0
⇔ 2x− 1 =0 hoặc x+ 2 =0
⇔ 2x =1 x = -2
⇔ x =\(\dfrac{1}{2}\) x = -2